Effects of an APOE Promoter Polymorphism on Fronto-Parietal Functional Connectivity During Nondemented Aging - Zhang, Qirui; Wu, Lingli; Du, Chao; Xu, Kai; Sun, Jinping; Zhang, Junying; Li, He; Li, Xin (Frontiers in Aging Neuroscience, 2020)
Background: The rs405509 polymorphism of the apolipoprotein E (APOE) promoter is related to Alzheimer’s disease (AD). The T/T allele of rs405509 is known to decrease the transcription of the APOE gene and lead to impairments in specific brain structural networks with ageing; thus, it is an important risk factor for AD. However, it remains unknown whether rs405509 affects brain functional connectivity in ageing. Methods: We investigated the effect of the rs405509 genotype (T/T vs G-allele) on age-related brain functional connectivity using functional magnetic resonance imaging. Forty-five elderly TT carriers and 45 elderly G-allele carriers were scanned during a working memory task. Results: We found that TT carriers showed an accelerated age-related increase in functional activation in the left postcentral gyrus compared with G-allele carriers. Furthermore, the functional connectivity between the left postcentral gyrus and some key regions during working memory performance, including the right caudal and superior frontal sulcus, was differentially modulated by age across rs405509 genotype groups. Conclusions: These results demonstrate that the rs405509 T/T allele of APOE causes an age-related brain functional decline in nondemented elderly people, which may be beneficial for understanding the neural mechanisms of rs405509-related cognitive ageing and AD pathogenesis.